1981
DOI: 10.1177/00220345810600090601
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dental Amalgams on Mercury Levels in Expired Air

Abstract: The expired air of a group of 48 persons, 40 with and eight without dental amalgam restorations, was analyzed for its mercury content before and after chewing. Expired air samples were collected in polyethylene bags, and a known quantity of each was pumped into the mercury detector for measurement. The results showed that examined subjects with dental amalgams had higher pre-chewing mercury levels in their expired air than those without amalgams. After chewing, these levels were increased an average of 15.6-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
3

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(66 citation statements)
references
References 5 publications
3
60
0
3
Order By: Relevance
“…Chewing has been pointed out by many authors as a factor strongly increasing the amount of mercury vapor emitted from restorations. The emission of mercury vapor after some minutes of inten se chewing is normally increased three-to fivefold , and sometimes by more than that , according to Abraham et al (38), Svare et al (39), Vimy & Lorscheider (40,41), and our unpublished results. In referen ce to these experiences the present result indicating only a weak influence from "chewing" was a surprise.…”
Section: Mercury Exposure Of Dentists and Dental Nursessupporting
confidence: 66%
“…Chewing has been pointed out by many authors as a factor strongly increasing the amount of mercury vapor emitted from restorations. The emission of mercury vapor after some minutes of inten se chewing is normally increased three-to fivefold , and sometimes by more than that , according to Abraham et al (38), Svare et al (39), Vimy & Lorscheider (40,41), and our unpublished results. In referen ce to these experiences the present result indicating only a weak influence from "chewing" was a surprise.…”
Section: Mercury Exposure Of Dentists and Dental Nursessupporting
confidence: 66%
“…However, several studies in the late 1970s and early 1980s determined that this was not the case. [13][14][15][16] A number of studies have attempted to quantify the amount of mercury vapor released from existing amalgam restorations. [16][17][18][19] The use of different methodologies in these studies, however, makes comparison of their results difficult, if not impossible.…”
Section: Mercury Release From Dental Amalgam Restorationsmentioning
confidence: 99%
“…Although several investigators had shown that mercury vapor is released from hardened dental amalgam (Gay et al, 1979;Svare et al, 1981;Abraham et al, 1984), Vimy and Lorscheider (1985a,b) were the first to perform systematic intra-oral mercury vapor measurements in order to estimate the daily intake of mercury from amalgam fillings. In interpreting each subject's intra-oral mercury vapor readings, however, Vimy and Lorscheider treated the measurements as though the subject were exposed to room air at those concentrations.…”
Section: Intra-oral Hg Vapor Measurementsmentioning
confidence: 99%
“…Gum chewing has been used in the majority of the studies published (Gay et al, 1979;Svare et al, 1981;Abraham et al, 1984;Vimy and Lorscheider 1985a,b;Ott et al, 1986;Aronsson et al, 1989;Berglund, 1990;Bjorkman and Lind, 1992). Toothbrushing has also been used (Patterson et al, 1985;Langworth et al, 1988b;Berglund, 1990;Berglund and Molin, 1996).…”
Section: Intra-oral Hg Vapor Measurementsmentioning
confidence: 99%